Justice beyond the State Outer Margins: Contending Forms of Antifascist Violence and Judiciary Prractices in the Spanish Civil War (1936-39) and Liberation-France (1944-45) - Ledesma, José Luis (PARTECIPAZIONE E CONFLITTO, 2022)
Although civil war scholarship focuses on the study of violence in internecine conflict, little attention has been paid to the ways in which extra-judiciary violence and the legal administration of justice interact. This article explores the relationship between state justice and extra-judiciary practices in two settings: Republican-held territories during the Spanish Civil War (1936-39) and the later stages of WWII and Liberation-France (1944-45). This paper challenges the view that the violence perpetrated by armed non-state agents flared and existed only because of state institutional justice was lacking, and until it was replaced by it. After a general overview of violence and justice in civil war settings, this article summarizes the differences and blurred boundaries between extra-judiciary violence and legal justice in both case studies; finally, it argues that exploring the complex links between "legal justice" and "illegal revolutionary violence" is a useful way to improve our understanding of revolutions and civil wars, as violence in those contexts constitutes a challenge to existing law and seeks to create new and non-conventional ways to implement justice.